Current Status and Challenge for Implementation in Clinical Application of Augmented Reality in Orthopedics Department at a Medical Center (International Journal of Studies in Nursing, 2021)
With technical development, artificial intelligence (AI) has been actively involving in the healthcare industry. Augmented reality (AR) is an interactive experience with the combination of virtual objects and a real-world environment, and the objects reside in the environment of the real world through computer-generated images for the purpose to enhance perceptual effects, which can be applied in the fields of medical education and clinical practice. Researchers have found that learning motives and interests may be raised by AR. At a medical center, the inter-specialty team from the Teaching Department and Rehabilitation Department jointly developed an AR Medical Education App, which involves 44 muscle strength and walking exercises, including 6 upper limb movements, 28 lower limb exercises, and 10 cardiorespiratory exercises. Various exercise packages can be designed by health caregivers based on patient’s needs in exercise. The Orthopedics Ward applied it in the respiration training for patients who underwent spinal surgery, preventing respiratory comorbidities. The improved postoperative pulmonary function has been found when compared with that before surgery, with statistical significance. Respiration, upper and lower limbs exercises were persistently performed in patients who underwent spinal surgery, which also has been incorporated in routine nursing care to add diverse options of patient education materials for nursing personnel. In the future, aspects that required further efforts include: expanded software equipment, simplified operation mode, increased user-friendly features for equipment, and expended plentifulness of contents.